Enhanced Photocatalytic Activity of CuWO4 Doped TiO2 Photocatalyst Towards Carbamazepine Removal under UV Irradiation - Chukwuka Bethel Anucha; Ilknur Altin; Emin Bacaksız; Tayfur Kucukomeroglu; Masho Hilawie Belay; Vassilis N. Stathopoulos (Separations, 2021)
Abatement of contaminants of emerging concerns (CECs) in water sources has been widely studied employing TiO2 based heterogeneous photocatalysis. However, low quantum energy yield among other limitations of titania has led to its modification with other semiconductor materials for improved photocatalytic activity. In this work, a 0.05 wt.% CuWO4 over TiO2 was prepared as a powder composite. Each component part synthesized via the sol-gel method for TiO2, and CuWO4 by co-precipitation assisted hydrothermal method from precursor salts, underwent gentle mechanical agitation. Homogenization of the nanopowder precursors was performed by zirconia ball milling for 2 h. The final material was obtained after annealing at 500 °C for 3.5 h. Structural and morphological characterization of the synthesized material has been achieved employing X-ray diffraction (XRD), Fourier transform infra-red (FTIR) spectroscopy, Brunauer–Emmett–Teller (BET) N2 adsorption–desorption analysis, Scanning electron microscopy-coupled Energy dispersive X-ray spectroscopy (SEM-EDS), Transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS), and UV-Vis diffuse reflectance spectroscopy (UV-vis DRS) for optical characterization. The 0.05 wt.% CuWO4-TiO2 catalyst was investigated for its photocatalytic activity over carbamazepine (CBZ), achieving a degradation of almost 100% after 2 h irradiation. A comparison with pure TiO2 prepared under those same conditions was made. The effect of pH, chemical scavengers, H2O2 as well as contaminant ion effects (anions, cations), and humic acid (HA) was investigated, and their related influences on the photocatalyst efficiency towards CBZ degradation highlighted accordingly.